Kaitan Gender dan Struktur Keluarga dengan Pemberian Intervensi Gizi Spesifik pada Anak Usia 6-23 Bulan (Journal of Telenursing (JOTING), 2024)
This study aimed to explore the relationship between gender and family structure by providing specific nutritional interventions to children aged 6-23 months. The method used was analytical observational with a cross-sectional approach. The research results from chi-square analysis showed that there was a significant relationship between the child's gender and family type and the provision of specific nutrition (p value